How Russian Spies Are Analyzing Data From China’s WeChat App - Krolik, Aaron; Sonne, Paul (The New York Times, 2025)
Moscow has long been suspicious of foreign messaging apps. WeChat’s weak encryption makes it vulnerable.
China
Keywords: China; Computer Security; Espionage and Intelligence Services; Federal Security Service; Instant Messaging; Mobile Applications; Putin; Vladimir V; Russia; Surveillance of Citizens by Government; WeChat (Mobile App)